The national prospect. - Abrams, Elliott; Adelson, Joseph (Commentary)
Presents The National Prospect, a symposium which addresses the question about the stability of the American institutions. Statement that the United States is moving towards balkanization or even breakdown; Reasons for statement; Responses from a group of American intellectuals.